Clinical profile and screening of exon 6 and 14 of ABCB4 gene in obstetric cholestasis patients at a tertiary care hospital in Rawalpindi, Pakistan - Nuzhat Noor; Sabika Firasat; Naheed Bano; Kiran Afshan; Bushra Gul; Haiba Kaul (Journal of the Pakistan Medical Association, 2021)
Objective: Intrahepatic Cholestasis of Pregnancy (ICP) is a rare pregnancy specific disorder. Genetic variants of ABCB4 gene increase ICP risk. This study was conducted to determine frequency of ICP cases presented at a tertiary care hospital in Rawalpindi, Pakistan and to screen for genetic variants of exon 6 and 14 of ABCB4 gene inICP cases. Methods: This analytical study included ICP patients presented at Department of Gynaecology and Obstetrics, Holy Family Hospital Rawalpindi, from February 2017 to May 2017. Sanger’s sequencing was performed using genomic DNA extracted from blood samples of patients and controls. Results: Twenty pregnant women out of 1150 (1.74%) had ICP and enrolled during study period. Overall 95% patients had pruritus and among them 40%, 20% and 10% had a history of miscarriages, stillbirths and familial ICP respectively. Genetic analysis revealed an already reported variant i.e., c.504C>T in exon 6 in thirteen patients and a novel variant i.e., c.1686A>G in exon 14 in five patients. Both variants were not present in controls. In silico analysis suggested that both variants might affect pre-mRNA splicing of ABCB4 transcript. Conclusion: ICP had a frequency of 1.74% among pregnant women. Identification of a novel heterozygous variant in five patients and an already reported variant in thirteen patients reaffirms genetic heterogeneity and role of ABCB4 in ICP etiology. Keywords: intrahepatic cholestasis of pregnancy, ABCB4 gene, Single Nucleotide Polymorphism (SNP), Continuous...